2010
DOI: 10.1007/s00464-010-1357-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic polymer–tissue adhesion using an ultrasonic scalpel

Abstract: Both polar functional groups and adequate thermal characteristics are necessary for polymers to bond with tissues. These findings should be useful for the development of novel polymers that can be bonded to living tissues with UAS treatment, which can be applied for endoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…The ionizing treatment altered the PE surface from hydrophobic to relatively hydrophilic by introducing mainly oxygen (Yamamoto et al 2011). The contact angle between liquid-solid interfaces is a good indicator of adsorption because it increases the capacity of the liquid to spread, thereby decreasing the contact angle (Rubin 2004).…”
Section: Contact Angle Measurements Of Ionized Filmsmentioning
confidence: 99%
“…The ionizing treatment altered the PE surface from hydrophobic to relatively hydrophilic by introducing mainly oxygen (Yamamoto et al 2011). The contact angle between liquid-solid interfaces is a good indicator of adsorption because it increases the capacity of the liquid to spread, thereby decreasing the contact angle (Rubin 2004).…”
Section: Contact Angle Measurements Of Ionized Filmsmentioning
confidence: 99%
“…In a previous work, using polymeric films as model materials, we found that functional groups and physical properties dominated material–tissue adhesion . These findings were based on the structural and physical properties of the material, which had bonded to tissue upon the application of heat and mechanical vibration generated by the blade of an ultrasonically activated scalpel .…”
Section: Introductionmentioning
confidence: 83%
“…The monomer was chosen based on the results of our previous study . The purchased acrylic acid (AA) (Wako Chemicals, Tokyo, Japan), methacrylic acid (MA) (Wako Chemicals, Tokyo, Japan), 4‐vinylbenzoic acid (VBA) (Kohjin, Tokyo, Japan), hydroxyethyl acrylate (HEA) (Wako Chemicals, Tokyo, Japan), and hydroxyethyl methacrylate (HEMA) (Wako Chemicals, Tokyo, Japan) were all distilled to eliminate moisture and the inhibitors and then kept in a cool and dark environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second stage at 65°C the resulting prepolymer is reacted with TPED or HMB, at the equimolar ratio of -NCO to -OH groups using DBTDL as a catalyst, getting macroinitiators in MEK solution, appropriately urethane-tetraphenylethane (TPE-PU-TPE) or bromourethane (MBP-PU-MBP) containing 0 wt% content of -NCO groups 14 . The TPE--PU-TPE macroinitiator synthesis process is presented by the following scheme: (5) where: R denotes part of the structure coming from TPE-PU-TPE or MBP-PU-MBP.…”
mentioning
confidence: 99%